2021
DOI: 10.4314/gjg.v13i1.12
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of households’ adoption behaviour of solar home systems (SHSS) in Ashongman Estate in the Greater Accra Region of Ghana

Abstract: Ghana heavily relies on hydrogenated and thermal electricity. For the past thirteen years, the dynamics of climate change and increasing fuel prices have engendered an electricity crisis since the supply of electricity cannot match the ever-burgeoning demand from households and industries. While this is so, the uptake of renewable energy sources has been abysmal in Ghana. This study thus seeks to assess the adoption behaviour of solar home systems, an environmentally friendly and convenient alternative electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Since the beginning of the ongoing global financial crisis in October 2008, international investors have sold local investors a total of 145 million USD worth of bonds that they owned. There is further evidence to suggest that the severe depreciation of the cedi in 2008 contributed considerably to the withdrawal of foreign investors from the market for government assets, which in turn caused an even larger decrease in the value of the cedi [37]. The fact that our government does not have any gold bars in its reserves is perhaps the single most important factor contributing to the devaluation of the cedi.…”
Section: Liberalization Of the Capital Market To Foreignersmentioning
confidence: 94%
See 1 more Smart Citation
“…Since the beginning of the ongoing global financial crisis in October 2008, international investors have sold local investors a total of 145 million USD worth of bonds that they owned. There is further evidence to suggest that the severe depreciation of the cedi in 2008 contributed considerably to the withdrawal of foreign investors from the market for government assets, which in turn caused an even larger decrease in the value of the cedi [37]. The fact that our government does not have any gold bars in its reserves is perhaps the single most important factor contributing to the devaluation of the cedi.…”
Section: Liberalization Of the Capital Market To Foreignersmentioning
confidence: 94%
“…According to [1]'s findings, the performance of the manufacturing sector in Ghana improves whenever the currency rate appreciates, and if it depreciates, the industry is badly affected, which in turn has a negative impact on the amount of employment in the nation. According to [37] 's findings, the depreciation of the Ghanaian cedi in comparison to the United States dollar considerably reduces the rate of job growth in the manufacturing sector in Ghana.…”
Section: Trends In Foreign Exchange Rate In Ghanamentioning
confidence: 99%
“…The basic flow of the algorithm is to process the element management set to be divided. The final output of the algorithm is many sets [4]. The elements in each collection have some of the same properties.…”
Section: Set Partition Methodsmentioning
confidence: 99%
“…Ghana has limited provisions of healthcare for PwDs despite the Disability Act, Act 2006, which aims to ensure access to effective healthcare and adequate medical rehabilitation services to members of this vulnerable group [ 17 ]. Meanwhile, PwDs are confronted with a myriad of barriers in accessing healthcare in Ghana, including health financing, structural and physical environment [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, PwDs are confronted with a myriad of barriers in accessing healthcare in Ghana, including health financing, structural and physical environment [ 18 ]. For instance, Mensah et al [ 17 ] reported that health facilities do not provide disability friendly services, making it difficult for most PwDs, especially those in wheelchairs to access hospital buildings and climb onto medical examination beds [ 19 ]. Accordingly, district accessibility audit data in Ghana, like that from Sekondi-Takoradi Metropolis (STM), revealed that 76.6% of medical centers lack internal policies targeting medical facility access for PwDs.…”
Section: Introductionmentioning
confidence: 99%